2023
DOI: 10.1021/jacs.2c12762
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Structural Motifs of Glycosaminoglycans using Cryogenic Infrared Spectroscopy and Random Forest

Abstract: In recent years, glycosaminoglycans (GAGs) have emerged into the focus of biochemical and biomedical research due to their importance in a variety of physiological processes. These molecules show great diversity, which makes their analysis highly challenging. A promising tool for identifying the structural motifs and conformation of shorter GAG chains is cryogenic gas-phase infrared (IR) spectroscopy. In this work, the cryogenic gas-phase IR spectra of mass-selected heparan sulfate (HS) di-, tetra-, and hexasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Especially, the nondestructive nature of the spectroscopy methods allows the in situ dynamic tracking of chemical and biological samples. When it comes to the real systems, due to the overwhelming contribution from the complicated matrix, it is hard to identify the spectral information from the target by naked eyes, which could only be realized with the introduction of chemometrics. In recent years, deep-learning-based chemometrics has grown rapidly owing to the explosion of data volumes and increased computer performance. The strong feature extraction of deep learning allows it to acutely identify and capture subtle differences between complex signals .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the nondestructive nature of the spectroscopy methods allows the in situ dynamic tracking of chemical and biological samples. When it comes to the real systems, due to the overwhelming contribution from the complicated matrix, it is hard to identify the spectral information from the target by naked eyes, which could only be realized with the introduction of chemometrics. In recent years, deep-learning-based chemometrics has grown rapidly owing to the explosion of data volumes and increased computer performance. The strong feature extraction of deep learning allows it to acutely identify and capture subtle differences between complex signals .…”
Section: Introductionmentioning
confidence: 99%
“…Support vector machines (SVM) and decision tree ensemble methods were benchmarked on infrared spectra for cancer classification [ 8 ] and many research groups focused their efforts on using machine learning for simulating molecular structures; generating vibrational spectra; and classifying chemical groups based on vibrational features [ 9 10 ]. In a recent publication, the random forest approach was proposed to identify the presence of structural features in oligosaccharides based on their gas-phase IR spectra [ 11 ]. To the best of our knowledge, machine learning classification studies have not been reported to identify saccharides using MS–IR carbohydrate analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the organic compounds are natural products or synthesized by chemists, it is extremely important to determine their structures and absolute conformations at the atomic level. Over the past few decades, numerous researchers have developed and refined many methods for the structural identification of organic molecules, such as nuclear magnetic resonance ( NMR ), infrared spectroscopy ( IR ), mass spectrometry ( MS ), single crystal X-ray diffraction ( X-ray SCD ), etc. Among them, X-ray SCD can provide direct and accurate structural information and is globally recognized as a fairly reliable method for the structural identification of organic compounds, including their stereochemical conformation.…”
mentioning
confidence: 99%